A heat exchange membrane with high efficient moisture permeability and its preparation method and application
Patent Information
- Application Number
- CN202411917067.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-12-24
AI Technical Summary
然而,传统热交换膜材料在长期使用过程中易滋生细菌,影响空气质量及设备性能,同时,其透湿性能也难以满足高效热交换的需求
[0020]本发明通过选择具有一定孔隙结构的多孔聚合物膜作为基膜,并通过在多孔基膜一面涂覆相应的亲水涂层浆料,使亲水涂层浆料可以渗透至多孔基膜的空隙内部,并到达多孔基膜的另一面,通过一次涂覆在多孔基膜的两面均形成均匀的亲水涂层并在多孔基膜的孔隙填充亲水材料,可有效提升热交换的气密性;多孔基膜两面的涂层通过孔隙内部填充的亲水材料连接,形成高效的透湿通路,提升热交换膜的透湿性能。本发明提供的热交换膜的制备方法可以实现一次涂覆双面亲水,涂覆效率高、成本低,可有效解决现有单面涂覆的方式形成双面涂层存在效率低、成本高的问题。
Smart Images

Figure CN119798771B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat exchange technology, and in particular to a heat exchange membrane with high moisture permeability, its preparation method, and its application. Background Technology
[0002] With technological advancements and rising living standards, residents are increasingly aware of the importance of healthy living environments, leading to a surge in demand for healthy fresh air systems. Heat exchangers, as a typical healthy fresh air device, are widely used in residential comfort settings. Their principle involves transferring the temperature and humidity of air exhausted from indoors to outdoors to the air supplied from outdoors, returning it indoors. Fresh air is purified through the heat exchanger's filter, then exchanges heat with indoor exhaust (or return) air within the heat exchange core before being delivered clean and comfortable fresh air into the room. This achieves the replenishment of fresh air to the indoor space, the removal of stale air, and the regulation of temperature and humidity. It utilizes indoor return air to pre-cool or pre-heat fresh air, maximizing the use of energy that was previously unavailable indoors, thereby reducing system energy consumption.
[0003] As a core component of a fresh air system, the total heat exchange core is crucial for delivering fresh air and creating a comfortable indoor environment. It primarily consists of a heat exchange membrane and a reinforcing element. The heat exchange membrane mainly functions as a heat conductor, a gas shield, and a moisture permeable material. However, traditional heat exchange membrane materials are prone to bacterial growth during long-term use, affecting air quality and equipment performance. Furthermore, their moisture permeability is insufficient to meet the demands of efficient heat exchange. Summary of the Invention
[0004] To address one or more technical problems existing in the prior art, this invention provides a heat exchange membrane with high moisture permeability, its preparation method, and its application. The heat exchange membrane provided by this invention has good airtightness, high moisture permeability, and excellent anti-mildew properties, which can meet the requirements of high-efficiency heat exchange cores for high moisture permeability and airtightness of heat exchange membranes.
[0005] The present invention provides, in a first aspect, a method for preparing a heat exchange membrane with high moisture permeability, the method comprising:
[0006] A supporting membrane is composited with a porous base membrane; the porous base membrane is a porous polymer membrane with a pore size of 100-1500 nm and a porosity of 35-70%.
[0007] A hydrophilic coating slurry is coated on one side of the porous base membrane and dried to form a hydrophilic coating on both sides of the porous base membrane, thereby obtaining a heat exchange membrane with high moisture permeability; the hydrophilic material in the hydrophilic coating slurry accounts for 15-40 wt%; the hydrophilic material is a sulfonate.
[0008] Preferably, the porous polymer membrane is one of a porous PE membrane, a porous PTFE membrane, a porous PVDF membrane, and a porous PP membrane; and / or
[0009] The support film has an operating temperature greater than 100°C and is preferably a PET film.
[0010] Preferably, the composite method adopts a press-and-wind method; during the press-and-wind process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is 0.5 to 2.5 m / s.
[0011] Preferably, the sulfonate is one or more of aminoalkyl sulfonate, sodium dodecylbenzene sulfonate, and biguanide trioctylbenzene sulfonate.
[0012] Preferably , The coating is performed by roller coating. During the roller coating process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is 0.3 to 0.8 m / s.
[0013] Preferably, the amount of hydrophilic material used during the roller coating process is controlled to be 5-7 g / m³. 2 .
[0014] Preferably, the drying temperature is 95–100°C and the drying time is 50–60 seconds.
[0015] Preferably, the process further includes a release winding step after drying; during the release winding process, the winding tension of the support film is greater than the winding tension of the heat exchange film; preferably, the winding tension of the support film is 2.5–4 kgf, and the winding tension of the heat exchange film is 0.5–1 kgf; and / or
[0016] During the release winding process, the winding speed of the support film and the heat exchange film is the same; preferably, the winding speed of the support film and the heat exchange film is 0.5 to 1 m / s.
[0017] In a second aspect, the present invention also provides a heat exchange membrane with high moisture permeability, which is prepared by the preparation method described in the first aspect.
[0018] In a third aspect, the present invention also provides an application of the heat exchange membrane with high moisture permeability described in the second aspect for use in a total heat exchange core.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects:
[0020] This invention selects a porous polymer membrane with a specific pore structure as the base membrane and coats one side of the porous base membrane with a corresponding hydrophilic coating slurry. This allows the hydrophilic coating slurry to penetrate into the pores of the porous base membrane and reach the other side. By coating both sides of the porous base membrane with a uniform hydrophilic coating in a single step and filling the pores with hydrophilic material, the airtightness of the heat exchange can be effectively improved. The coatings on both sides of the porous base membrane are connected by the hydrophilic material filling the pores, forming an efficient moisture permeability pathway and improving the moisture permeability of the heat exchange membrane. The heat exchange membrane preparation method provided by this invention can achieve double-sided hydrophilic coating in a single step, with high coating efficiency and low cost, effectively solving the problems of low efficiency and high cost associated with existing single-sided coating methods for forming double-sided coatings.
[0021] The heat exchange membrane provided by this invention has good airtightness, high moisture permeability and excellent mildew resistance, which can meet the requirements of high-efficiency heat exchange cores for high moisture permeability and airtightness of heat exchange membranes. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the cross-sectional structure of the heat exchange membrane with high moisture permeability provided by the present invention.
[0024] Figure reference numerals: 11-porous base membrane; 12-hydrophilic coating. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] The present invention provides, in a first aspect, a method for preparing a heat exchange membrane with high moisture permeability, the method comprising:
[0027] The supporting membrane is composited with the porous base membrane 11; the porous base membrane 11 is a porous polymer membrane with a pore size of 100-1500 nm (e.g., 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm or 1500 nm) and a porosity of 35-70% (e.g., 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%).
[0028] A hydrophilic coating slurry is coated on one side of the porous base membrane and dried to form a hydrophilic coating 12 on both sides of the porous base membrane 11, thereby obtaining a heat exchange membrane with high moisture permeability. The hydrophilic material in the hydrophilic coating slurry accounts for 15-40 wt% (for example, it can be 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, or 40 wt%), preferably 20-40 wt%. The hydrophilic material is a sulfonate.
[0029] This invention selects a porous polymer membrane with a specific pore structure as the base membrane and coats one side of the porous base membrane with a corresponding hydrophilic coating slurry. This allows the hydrophilic coating slurry to penetrate into the pores of the porous base membrane and reach the other side. By coating both sides of the porous base membrane with a uniform hydrophilic coating in a single step and filling the pores with hydrophilic material, the airtightness of the heat exchange can be effectively improved. The coatings on both sides of the porous base membrane are connected by the hydrophilic material filling the pores, forming an efficient moisture permeability pathway and improving the moisture permeability of the heat exchange membrane. The heat exchange membrane preparation method provided by this invention can achieve double-sided hydrophilic coating in a single step, with high coating efficiency and low cost, effectively solving the problems of low efficiency and high cost associated with existing single-sided coating methods for forming double-sided coatings.
[0030] The heat exchange membrane provided by this invention has good airtightness, high moisture permeability and excellent mildew resistance, which can meet the requirements of high-efficiency heat exchange cores for high moisture permeability and airtightness of heat exchange membranes.
[0031] The structure of the porous base membrane (pore distribution and size) and the concentration of the hydrophilic coating slurry in this invention jointly determine whether the hydrophilic coating slurry can penetrate into the pores of the porous base membrane and the other side of the base membrane, forming an effective hydrophilic coating on both sides of the base membrane, thus obtaining a heat exchange membrane with moisture permeability. Based on this, this invention selects a porous polymer membrane with uniform pore distribution, a pore size of 100–1500 nm, and a porosity of 35–70% as the base membrane. Given a fixed base membrane, the concentration of the hydrophilic coating slurry (the content of hydrophilic materials in the hydrophilic coating slurry) is crucial. If the concentration is too low, an effective hydrophilic coating cannot be formed, and the improvement in the moisture permeability of the porous polymer membrane is minimal. If the concentration is too high, the hydrophilic material molecules may form aggregates or micelle structures, blocking the membrane pores, preventing the slurry from penetrating to the other side of the porous base membrane, and failing to achieve a uniform hydrophilic coating on both sides of the base membrane in a single application, which is also detrimental to improving the moisture permeability of the porous polymer membrane.
[0032] According to some preferred embodiments, the porous polymer membrane is one of porous PE membrane, porous PTFE membrane, porous PVDF membrane, and porous PP membrane.
[0033] According to some preferred embodiments, the operating temperature of the support film is greater than 100°C, and it is preferably a PET film.
[0034] Because porous polymer membranes generally have poor high-temperature resistance, they shrink and deform at around 80-90°C, while the hydrophilic coating dries completely at around 100°C. Therefore, this invention combines a support film with excellent physical and mechanical properties and a service temperature above 100°C with the porous polymer membrane by pressing and winding it before coating. The support film's supporting effect on the porous polymer membrane effectively improves the problem of thermal shrinkage that easily occurs during the drying process. The support film of this invention is preferably a PET film with excellent physical and mechanical properties and a service temperature up to 120°C.
[0035] According to some preferred embodiments, the composite method adopts a press-and-wind method; during the press-and-wind process, the winding tension of the support film is controlled to be 2.5 to 4 kgf, and the winding speed is 0.5 to 2.5 m / s.
[0036] This invention controls the winding tension and winding speed within the above-mentioned range during the composite process of the support membrane and the porous polymer membrane, which can ensure better composite of the porous polymer membrane and the support membrane without damaging the support membrane.
[0037] According to some preferred embodiments, the sulfonate is one or more selected from aminoalkyl sulfonate, sodium dodecylbenzenesulfonate, and biguanide trioctylbenzenesulfonate. The types of sulfonates in this invention are not limited to the above scope; the sulfonates described above are merely for illustrative purposes and not for limitation.
[0038] To achieve a single-coat hydrophilic layer on both sides of a porous substrate, different sulfonates require different concentrations of the hydrophilic coating slurry and different pore structures of the substrate. Specifically: when the sulfonate is sodium dodecylbenzenesulfonate, the concentration of the hydrophilic coating slurry is 20–40% (sodium dodecylbenzenesulfonate accounts for 20–40 wt% of the hydrophilic coating slurry), the pore size of the porous polymer membrane is 100–600 nm, and the porosity is 35–40%. When the sulfonate is an aminoalkyl sulfonate, the concentration of the hydrophilic coating slurry is 15–30% (aminoalkyl sulfonate accounts for 15–30 wt% of the hydrophilic coating slurry), the pore size of the porous polymer membrane is 100–600 nm, and the porosity is 35–40%. When the sulfonate is biguanide trioctylbenzene sulfonate, the concentration of the hydrophilic coating slurry is 30-40% (biguanide trioctylbenzene sulfonate accounts for 30-40 wt% in the hydrophilic coating slurry), the pore size of the porous polymer membrane is 500-1500 nm, and the porosity is 40-70%.
[0039] According to some preferred embodiments , The coating is performed using a roller coating method. During the roller coating process, the winding tension of the supporting membrane is controlled at 2.5–4 kgf, and the winding speed is 0.3–0.8 m / s. This invention ensures that the hydrophilic coating slurry can fully penetrate to the other side of the porous base membrane and fill the pores by controlling the winding tension and winding speed of the supporting membrane during roller coating, forming an effective double-sided hydrophilic coating and creating a highly efficient moisture permeability pathway. Under the same conditions, if the winding speed is too high, the hydrophilic coating slurry will not be able to fully penetrate to the other side of the porous base membrane and fill the pores, resulting in poor moisture permeability and airtightness of the heat exchange membrane, and consequently, a decrease in its anti-mildew performance. If the winding speed is too low, although a double-sided hydrophilic coating can be formed, the efficiency is too low, and the efficiency improvement compared to using a double-sided coating method is not significant.
[0040] According to some preferred embodiments, the amount of hydrophilic material used in the roller coating process is controlled to be 5-7 g / m². 2 This invention controls the amount of hydrophilic coating slurry and the coating speed (winding speed) during the roll coating process to ensure that the hydrophilic coating slurry can penetrate to the other side of the porous base membrane and fully fill the microporous structure of the base membrane, thereby obtaining a heat exchange membrane with excellent airtightness and moisture permeability.
[0041] According to some preferred embodiments, the drying temperature is 95-100°C and the time is 50-60 seconds.
[0042] According to some preferred embodiments, a release winding step is further included after the drying process; during the release winding process, the winding tension of the support film is greater than the winding tension of the heat exchange film; preferably, the winding tension of the support film is 2.5–4 kgf, and the winding tension of the heat exchange film is 0.5–1 kgf; and / or
[0043] During the release winding process, the winding speed of the support film and the heat exchange film is the same; preferably, the winding speed of the support film and the heat exchange film is 0.5 to 1 m / s.
[0044] This invention separates the support film and the heat exchange film by release winding after drying. During the winding process, the winding tension of the support film is controlled to be greater than that of the heat exchange film, and the winding speeds of the support film and the heat exchange film are the same, so as to ensure that the two are separated without damaging the support film and the heat exchange film.
[0045] In a second aspect, the present invention also provides a heat exchange membrane with high moisture permeability, which is prepared by the preparation method described in the first aspect.
[0046] In a third aspect, the present invention also provides an application of the heat exchange membrane with high moisture permeability described in the second aspect for use in a total heat exchange core.
[0047] The heat exchange membrane provided by this invention has good airtightness, high moisture permeability and excellent mildew resistance, which can meet the requirements of high-efficiency heat exchange cores for high moisture permeability and airtightness of heat exchange membranes.
[0048] To more clearly illustrate the technical solution and advantages of the present invention, the present invention will be further described below with reference to embodiments. The present invention does not specifically limit the source of the reagents used in the embodiments and comparative examples; they can be directly purchased or synthesized in-house.
[0049] Example 1
[0050] The supporting film (PET film) and the porous base film (porous PE film, 18 μm thick, 100 nm in pore size, and 35% porosity) are laminated by pressing and winding. During the pressing and winding process, the winding tension of the supporting film is 2.5 kgf and the winding speed is 0.5 m / s.
[0051] A hydrophilic coating slurry (obtained by dissolving sodium dodecylbenzenesulfonate in water, wherein sodium dodecylbenzenesulfonate accounts for 20 wt% of the hydrophilic coating slurry) was roll-coated onto the surface of the composite porous base membrane. During the roll-coating process, the winding tension of the support membrane was controlled at 2.5 kgf, the winding speed at 0.3 m / s, and the amount of hydrophilic material used during the roll-coating process was 7 g / m. 2The composite membrane after being coated with the hydrophilic coating slurry by roller is dried at a temperature of 100℃ for 50 seconds. The dried composite membrane is then released and wound up. During the release and winding process, the winding tension of the support membrane is 2.5 kgf and the winding tension of the heat exchange membrane is 0.5 kgf. The winding speed of the support membrane and the heat exchange membrane is 1 m / s, resulting in a heat exchange membrane with high moisture permeability.
[0052] Example 2
[0053] A composite film was obtained by pressing and winding a support film (PET film) and a porous base film (porous PE film, 18 μm thick, 400 nm pore size, and 40% porosity) together. The winding tension of the support film during the pressing and winding process was 2.5 kgf, and the winding speed was 0.5 m / s.
[0054] A hydrophilic coating slurry (obtained by dissolving sodium dodecylbenzenesulfonate in water, wherein sodium dodecylbenzenesulfonate accounts for 40 wt% of the hydrophilic coating slurry) was roll-coated onto the surface of the composite porous base membrane. During the roll-coating process, the winding tension of the support membrane was controlled at 2.5 kgf, the winding speed at 0.3 m / s, and the amount of hydrophilic material (sodium dodecylbenzenesulfonate) used during the roll-coating process was 5 g / m. 2 The composite membrane after being coated with the hydrophilic coating slurry by roller is dried at a temperature of 100℃ for 50 seconds. The dried composite membrane is then released and wound up. During the release and winding process, the winding tension of the support membrane is 2.5 kgf and the winding tension of the heat exchange membrane is 0.5 kgf. The winding speed of the support membrane and the heat exchange membrane is 1 m / s, resulting in a heat exchange membrane with high moisture permeability.
[0055] Example 3
[0056] A composite film was obtained by pressing and winding a support film (PET film) and a porous base film (porous PE film, 18 μm thick, 600 nm pore size, and 40% porosity) together. The winding tension of the support film during the pressing and winding process was 2.5 kgf, and the winding speed was 0.5 m / s.
[0057] A hydrophilic coating slurry (obtained by dissolving aminoalkyl sulfonate in water, wherein the aminoalkyl sulfonate accounts for 30 wt% of the hydrophilic coating slurry) was roll-coated onto the surface of the composite porous base membrane. During the roll-coating process, the winding tension of the support membrane was controlled at 2.5 kgf, the winding speed at 0.3 m / s, and the amount of hydrophilic material (aminoalkyl sulfonate) used during the roll-coating process was 6 g / m. 2The composite membrane after being coated with the hydrophilic coating slurry by roller is dried at a temperature of 100℃ for 50 seconds. The dried composite membrane is then released and wound up. During the release and winding process, the winding tension of the support membrane is 2.5 kgf and the winding tension of the heat exchange membrane is 0.5 kgf. The winding speed of the support membrane and the heat exchange membrane is 1 m / s, resulting in a heat exchange membrane with high moisture permeability.
[0058] Example 4
[0059] A composite film was obtained by pressing and winding a support film (PET film) and a porous base film (porous PE film, 18 μm thick, 1500 nm pore size, and 70% porosity) together. The winding tension of the support film during the pressing and winding process was 2.5 kgf, and the winding speed was 0.5 m / s.
[0060] A hydrophilic coating slurry (obtained by dissolving biguanide trioctylbenzene sulfonate in water, wherein biguanide trioctylbenzene sulfonate accounts for 40 wt% of the hydrophilic coating slurry) was roll-coated onto the surface of the composite porous base membrane. During the roll-coating process, the winding tension of the support membrane was controlled at 2.5 kgf, the winding speed at 0.8 m / s, and the amount of hydrophilic material (biguanide trioctylbenzene sulfonate) used during the roll-coating process was 7 g / m. 2 The composite membrane after being coated with the hydrophilic coating slurry by roller is dried at a temperature of 100℃ for 50 seconds. The dried composite membrane is then released and wound up. During the release and winding process, the winding tension of the support membrane is 2.5 kgf and the winding tension of the heat exchange membrane is 0.5 kgf. The winding speed of the support membrane and the heat exchange membrane is 1 m / s, resulting in a heat exchange membrane with high moisture permeability.
[0061] Example 5
[0062] The results are basically the same as in Example 2, except that the porous base film is a porous PTFE film (thickness of 18 μm, pore size of 400 nm, and porosity of 40%).
[0063] Example 6
[0064] The results are basically the same as in Example 2, except that the porous base film is a porous PVDF film (thickness of 18 μm, pore size of 400 nm, and porosity of 40%).
[0065] Example 7
[0066] The results are basically the same as in Example 2, except that the porous base film is a porous PP film (thickness of 18 μm, pore size of 400 nm, and porosity of 40%).
[0067] Comparative Example 1
[0068] It is basically the same as Example 2, except that the porous base membrane is a porous PE membrane (pore size of 50nm, porosity of 20%).
[0069] Comparative Example 2
[0070] It is basically the same as Example 2, except that the porous base membrane is a porous PE membrane (pore size of 2000nm, porosity of 80%).
[0071] Comparative Example 3
[0072] This is essentially the same as Example 2, except that sodium dodecylbenzenesulfonate accounts for 5 wt% of the hydrophilic coating slurry.
[0073] Comparative Example 4
[0074] This is essentially the same as Example 2, except that sodium dodecylbenzenesulfonate accounts for 50 wt% of the hydrophilic coating slurry.
[0075] Comparative Example 5
[0076] It is basically the same as Example 2, except that the winding speed of the support film during the roll coating process is 1.5m / s.
[0077] Comparative Example 6
[0078] It is basically the same as Example 2, except that the porous base film and the support film are not combined during the roll coating process.
[0079] Experimental results show that the porous base film (porous PE film) has an excessively high thermal shrinkage rate (25%) during the drying process due to the lack of composite support film, and the insufficient mechanical strength of the porous base film (porous PE film) makes it impossible to wind up and coat with slurry.
[0080] Comparative Example 7
[0081] It is basically the same as Example 5, except that there is no support film during the roll coating process.
[0082] Experimental results show that the porous base film (porous PTFE film) has an excessively high thermal shrinkage rate (12%) during the drying process due to the lack of composite support film, and the insufficient mechanical strength of the porous base film (porous PTFE film) makes it impossible to wind up and coat with slurry.
[0083] Comparative Example 8
[0084] It is basically the same as Example 6, except that there is no support film during the roll coating process.
[0085] Experimental results show that although the porous base film (porous PVDF film) has good temperature resistance (heat shrinkage rate of only 5%), the insufficient mechanical strength of the porous base film (porous PVDF film) itself makes it impossible to wind up and coat with slurry.
[0086] Comparative Example 9
[0087] It is basically the same as Example 7, except that there is no support film during the roll coating process.
[0088] Experimental results show that the porous base film (porous PP film) has an excessively high thermal shrinkage rate (70%) during the drying process due to the lack of composite support film, and the insufficient mechanical strength of the porous base film (porous PP film) makes it impossible to wind up and coat with slurry.
[0089] The performance data of the heat exchange membranes prepared in the various embodiments and comparative examples of the present invention are shown in Table 1. The test methods are as follows:
[0090] Heat shrinkage rate: The test method refers to GB / T 17313-1998 "Test method for heat shrinkage rate". The test temperature is usually 90℃ and the test time is 1h.
[0091] Air tightness: The test method refers to GB / T 1038-2000 "Test method for gas permeability of plastic films and sheets - differential pressure method": This standard specifies the method for determining the gas permeability of plastic films and sheets using the differential pressure method.
[0092] Moisture permeability: The test method refers to GB / T 1037-2021 Determination of water vapor permeability of plastic films and sheets by cup weight gain and weight loss method and GB / T 17146-2015 Test method for water vapor permeability of building materials and their products.
[0093] Anti-mold rating: Under conditions of temperature 25℃~30℃ and relative humidity not less than 85%, the film is sealed on the petri dish. After 28 days of cultivation, the surface is observed under a magnifying glass to check for mold penetration. Generally, the standard for anti-mold testing of building materials is GB / T 1741-2007.
[0094] Table 1. Performance data of heat exchange membranes in embodiments and comparative examples of the present invention
[0095]
[0096] It should be noted that the differences in airtightness and moisture permeability in Examples 1-4 are due to differences in the pore structure of the base membrane, the type, concentration, and amount of hydrophilic material. The differences in moisture permeability in Examples 2 and 5-7 are mainly determined by the moisture permeability of the PTFE membrane, PVDF membrane, and PP membrane themselves.
[0097] The moisture permeability of the porous base membranes in Examples 2 and 5-7 was tested in this invention, and the moisture permeability was no greater than 4.5 g / (m³). 2 As shown in Table 1, the heat exchange membrane provided by this invention has good airtightness (not less than -0.09 MPa) and high moisture permeability (moisture permeability not less than 5.9 g / (m³)). 2 It has excellent anti-mildew properties (mildew resistance level 0), and its performance is significantly better than that of porous base membranes. It can meet the requirements of high-efficiency heat exchange cores for high moisture permeability and airtightness of heat exchange membranes.
[0098] Compared to Example 2, in Comparative Example 1, the porous base membrane had too small a pore size and porosity, preventing the hydrophilic coating slurry from fully penetrating to the other side of the membrane, resulting in poor moisture permeability and airtightness of the heat exchange membrane. In Comparative Example 2, the porous base membrane had too large a pore size and porosity, preventing the hydrophilic material from effectively filling the pores, leading to poor airtightness of the heat exchange membrane. Furthermore, the inability to form an efficient moisture permeability pathway resulted in poor moisture permeability, consequently reducing its anti-mildew performance. In Comparative Example 3, the concentration of the hydrophilic coating slurry was too low. Although the slurry could penetrate to the other side of the porous base membrane, the insufficient content of hydrophilic material prevented the formation of an effective double-sided hydrophilic coating and adequate filling of the pores, resulting in poor moisture permeability and airtightness of the heat exchange membrane, and consequently reducing its anti-mildew performance. In Comparative Example 4, due to the excessively high concentration of the hydrophilic coating slurry, hydrophilic material molecules formed aggregates or micelle structures, clogging the pores of the base membrane. This prevented the slurry from penetrating to the other side of the porous base membrane, thus failing to achieve a uniform hydrophilic coating on both sides of the porous base membrane in a single application. Consequently, the moisture permeability and airtightness of the heat exchange membrane deteriorated, leading to a decrease in its anti-mildew performance. In Comparative Example 5, due to the excessively fast winding speed, the slurry could not fully penetrate to the other side of the porous base membrane and fill the pores, failing to form an effective double-sided hydrophilic coating. This also resulted in poor moisture permeability and airtightness of the heat exchange membrane, further reducing its anti-mildew performance.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a heat exchange membrane with high moisture permeability, characterized in that, The preparation method includes: A supporting membrane is composited with a porous base membrane; the porous base membrane is a porous polymer membrane with a pore size of 100~1500nm and a porosity of 35~70%; the composite method is a press-and-wind method; during the press-and-wind process, the winding tension of the supporting membrane is controlled at 2.5~4kgf and the winding speed is 0.5~2.5m / s. A hydrophilic coating slurry is coated on one side of the porous base membrane and dried to form a hydrophilic coating on both sides of the porous base membrane, thereby obtaining a heat exchange membrane with high moisture permeability. The hydrophilic material in the hydrophilic coating slurry accounts for 15-40 wt%; the hydrophilic material is a sulfonate; the sulfonate is one or more of aminoalkyl sulfonate, sodium dodecylbenzene sulfonate, and biguanide trioctylbenzene sulfonate. The coating is performed using a roller coating method. During the roller coating process, the winding tension of the support film is controlled at 2.5~4 kgf, and the winding speed is controlled at 0.3~0.8 m / s; the amount of the hydrophilic material is controlled at 5~7 g / m. 2 .
2. The preparation method according to claim 1, characterized in that, The porous polymer membrane is one of porous PE membrane, porous PTFE membrane, porous PVDF membrane, and porous PP membrane.
3. The preparation method according to claim 1, characterized in that, The operating temperature of the support membrane is greater than 100°C.
4. The preparation method according to claim 3, characterized in that, The supporting film is a PET film.
5. The preparation method according to claim 1, characterized in that, The drying temperature is 95~100℃ and the time is 50~60s.
6. The preparation method according to claim 1, characterized in that, The drying process also includes a release and winding step; During the release winding process, the winding tension of the support film is greater than that of the heat exchange film.
7. The preparation method according to claim 6, characterized in that, The winding tension of the support membrane is 2.5~4 kgf, and the winding tension of the heat exchange membrane is 0.5~1 kgf.
8. The preparation method according to claim 6, characterized in that, During the release winding process, the winding speed of the support film and the heat exchange film is the same.
9. The preparation method according to claim 8, characterized in that, The winding speed of the support membrane and the heat exchange membrane is 0.5~1m / s.
10. A heat exchange membrane with high moisture permeability, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.
11. An application of the heat exchange membrane with high moisture permeability as described in claim 10, characterized in that, Used for total heat exchange cores.
Citation Information
Patent Citations
Moisture-permeable film for total heat exchange element, and total heat exchange element
CN116940797A